12 weeks ombitasvir/paritaprevir–ritonavir + ribavirin achieve high SVR rates in HCV-4 patients with advanced fibrosis. Issue 7 (July 2018) - Degasperi, Elisabetta; Aghemo, Alessio; Paolucci, Stefania; D'Ambrosio, Roberta; Borghi, Marta; Perbellini, Riccardo; Novazzi, Federica; De Nicola, Stella; Lunghi, Giovanna; Baldanti, Fausto; Lampertico, Pietro
Abstract: Background: Ombitasvir/paritaprevir–ritonavir (OBT/PTV–r) plus ribavirin (RBV) for 12 weeks in hepatitis C virus (HCV) genotype 4 patients with advanced fibrosis has been only investigated in clinical trials. Aims: To assess safety and efficacy of OBT/PTV–r + RBV for 12 weeks in real-life HCV-4 patients with advanced fibrosis. Methods: HCV-4 patients with advanced fibrosis consecutively receiving OBT/PTV–r + RBV for 12 weeks in a single center were enrolled. Fibrosis was staged by transient elastography (TE) (F3: ≥10 kPa; F4 ≥11.9 kPa) or histologically. Sustained virological response (SVR) was defined as undetectable HCV-RNA 12 weeks post-treatment. Results: Between January 2016 and February 2017, 49 HCV-4 patients were included: median age 54 (39–72) years, 84% males, 59% Egyptians, 35% fibrosis F3 and 65% F4, all Child Pugh class A. Median RBV dose was 1200 (200–1200) mg/day. At ITT analysis, 47 (96%) patients achieved an SVR (100% at PP analysis). SVR was not affected by ancestry (Egyptian vs. Italian 97% vs. 95%, p = 1.0), fibrosis stage (F3 vs. F4 100% vs. 94%, p = .53), presence of baseline resistance associated substitutions (RASs) or RBV reduction. Conclusions: We report 100% SVR with 12-weeks of OBT/PTV–r + RBV in HCV-4 patients with advanced liver disease, including compensated cirrhotics.